MEDIA PEMBELAJARAN KIMIA TERPADU PADA MADARASAH TSANAWIYAH NEGERI (MAN) 2 KOTA BENGKULU - Sari, Herlina Latipa Latipa; Negara, Edi Kusuma (Jurnal Media Infotama, 2011)
The research aims to create a Media Learning Chemistry Using Macromedia Flash 8.0. Chemistry Learning Media's where there is writing, animation and images. From the discussion it could be concluded that in the Chemistry Learning Media can provide another alternative for teachers in the subjects of Chemistry and the material presented is more interesting because of the presence of some text and image animations.The method used in this research is the development of the system, and method of data collection in a way, literature study, observation, and interviews.From the analysis and discussion, it can be deduced that the presence of Chemistry Integrated Science Learning Media is expected to attract the students' interest, and Integrated Science Chemistry Learning Media also provides an alternative to the teacher in presenting material on the Integrated Science Chemistry MTs.N 2 Bengkulu city.Keywords: Learning Media, Macromedia Flash 8.0, Chemistry